Prognostic impact of elevated fatty acid‐binding protein 1 in patients with heart failure. (4th February 2021) - Kagami, Kazuki; Sunaga, Hiroaki; Sorimachi, Hidemi; Harada, Tomonari; Yoshida, Kuniko; Kato, Toshimitsu; Kurosawa, Koji; Kawakami, Ryo; Koitabashi, Norimichi; Iso, Tatsuya; Adachi, Takeshi; Kurabayashi, Masahiko; et al.
Abstract: Aims: Few biomarkers to evaluate pathophysiological changes in extra‐cardiac tissues have been identified in patients with heart failure (HF). Fatty acid‐binding protein 1 (FABP), also known as liver FABP, is predominantly expressed in the liver. Circulating FABP1 has been proposed to be a sensitive biomarker for liver injury. However, little is known about the potential role of FABP1 as a biomarker for HF. Methods and results: Measurements of serum FABP1 and echocardiography were performed in subjects with compensated HF ( n  = 162) and control subjects without HF ( n  = 20). Patients were prospectively followed‐up for a composite outcome of all‐cause mortality or HF hospitalization. Compared with control subjects, levels of FABP1 were elevated in HF patients [7.9 (6.4–11.7) vs. 17.6 (10.4–28.9) ng/mL, P  < 0.0001]. There were significant correlations between FABP1 levels and estimated right ventricular systolic pressure and right atrial pressure. During a median follow‐up of 12.0 months, there were 55 primary composite endpoints in the HF cohort. The highest FABP1 tertile was associated with a three‐fold increased risk of the composite outcome compared with the lowest tertile [95% confidence interval (1.46–6.68), P  = 0.003], but other conventional hepatobiliary markers did not predict the outcome. After adjusting for age, sex, atrial fibrillation, and N‐terminal pro‐B‐type natriuretic peptide levels, serum FABP1 remained independently associated with the outcome. Adding FABP1 to the model based on clinical factors and N‐terminal pro‐B‐type natriuretic peptide significantly improved the prognostic value (global χ 2 20.8 vs. 15.5, P  = 0.01). Conclusion: Serum FABP1 levels are elevated in compensated HF patients, and the magnitude of elevation is independently associated with pulmonary hypertension, right atrial hypertension, and worse clinical outcomes. FABP1 may serve as a new potential biomarker for the assessment of hitherto unrecognized derangement of cardio‐hepatic interaction in HF.